A dose response study of the effect of prostaglandin E2 on thermal nociceptive sensitivity. (November 2017) - Domenichiello, Anthony F.; Wilhite, Breanne C.; Keyes, Gregory S.; Ramsden, Christopher E.
Abstract: Inhibition of prostaglandin (PG) biosynthesis has been used to relieve pain for thousands of years. Today non-steroidal anti-inflammatory drugs (which largely inhibit PG synthesis) are widely used to treat pain. Four main types of PGs (PGD2, PGE2, PGF2 and PGI2) are synthesized from arachidonic acid during inflammation and have been demonstrated to impact nociception. PGE2 has been the most studied and utilized for its pain producing properties and has been demonstrated to increase hypersensitivity in rodent nociceptive behavioral models when applied centrally and/or peripherally. Surprisingly, there are no published reports that use withdrawal from radiant light beam (Hargreaves apparatus) to examine the dose response effect of peripherally applied PGE2 on thermal nociceptive hypersensitivity. To address this gap in the literature, we performed a dose response study examining the effect of PGE2 on thermal hypersensitivity (assessed using a Hargreaves apparatus) where rats were injected with 0.003–30 μg of PGE2, intradermally into the hindpaw. Thermal hypersensitivity was assessed by measuring withdraw latency from a radiant light beam (Hargreaves test) and our primary objective was to determine the dose of PGE2 causing the most pronounced increase in thermal hypersensitivity (i.e. lowest withdraw latency). A secondary objective was to determine the minimum dose of PGE2 required to cause statistically significant decreases in thermal withdrawal latency as compared to rats injected with vehicle. We found that rats injected with the 30 μg dose of PGE2 exhibited the most pronounced thermal nociceptive hypersensitivity though secondary analysis showed that rats injected with PGE2 doses of 0.03–30 μg had lower withdrawal latencies as compared to rats injected with vehicle. This work fills an evidence gap and provides context to guide dose selection in future rodent pain behavior studies. Highlights: Prostaglandins are the most researched lipid mediators involved in pain and inflammation. PGE2 is the main prostaglandin studied in inflammatory pain. There are no dose response studies measuring the effect of PGE2 on thermal hypersensitivity using standard techniques. We measured the effect of different doses of PGE2 on thermal hypersensitivity by using a Hargreaves apparatus. Maximally effective PGE2 dose was 10-100 times higher than doses used in literature